Preservasi jalan secara long segment ruas jalan Wawotobi – Lasolo - Sakti, Putra; Nasrul , Nasrul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The implementation of long segment-based contracts which is considered new for service users and large contractors, the implementation of roads. So it is necessary to understand the system. The parties have difficulty implementing the standards that have been determined and understanding the scope of the work being carried out, resulting in the implementation of long segment-based work not being carried out effectively until now. Seeing the above problems, this research was carried out to The method used in this study uses the Importance perpormance analysis (IPA) questionnaire method. In accordance with the limitations of this study, the number of respondents used was 30 service users and 30 service providers at the Southeast Sulawesi Road Implementation CenterThe method used in this study used the Importance perpormance analysis (IPA) questionnaire method. In accordance with the limitations of this study, the number of respondents used was 30 service users and 30 providers Factors of understanding from Officials Commitment Makers (PPK) as service users place understanding in contract law as the dominant factor with weight (0.195), while service providers/contractors place the ability to understand contract law as the dominant factor with weight (0.206).